Resourcing and talent management : the theory and practice of recruiting and developing a workforce - Taylor, Stephen, 1965- (London ; New York : Kogan Page, 2025)
Covering the recruitment, selection and retention of staff as well as retirement, dismissals and redundancy, this is an essential textbook for the CIPD Advanced module in Strategic Resourcing and Talent Management. Resourcing and Talent Management outlines the key topics needed by HR master's students in their study of people resourcing and staff development. It covers everything from job design and both internal and external recruitment through to interviewing, selection and contracts of employment. There is also guidance on staff retention, succession planning and coverage of how staff leave the business whether through retirement, redundancy or dismissal. This ninth edition now includes new content on strategies for performance management and resourcing and talent management, guidance on upskilling staff when the skills the business needs are constantly evolving and additional material on the continuation of hybrid and remote working. Fully updated throughout, this textbook includes 'explore further' boxes to encourage students to read more deeply, reflective questions to support reflection on learning and activities to put their learning in practice and test their understanding. Online resources include lecturer manuals, PowerPoint slides and additional weblinks.
Učebnice poskytuje komplexní přehled řízení lidských zdrojů od náboru a výběru zaměstnanců po jejich rozvoj, motivaci a odchod z organizace. Zaměřuje se na strategické plánování, udržení talentů a moderní trendy, jako je hybridní práce či rozvoj dovedností v měnícím se pracovním prostředí. Publikace je určena studentům a odborníkům v oblasti personálního řízení a rozvoje pracovníků.
Obsahuje bibliografické odkazy a rejstřík
Keywords: personální management; lidský kapitál; talent management; přijímací řízení; učebnice; personnel management; human capital; talent management; employee selection; textbooks